Investigating the quality-of-life scale in patients with placental adhesion disorder undergoing a cesarean hysterectomy and partial uterine resection - Tanrıdan Okçu, Nefise; Uysal, Gulsum; Gürbüz, Tuğba; Nazik, Hakan; Narin, Raziye (The European Research Journal, 2022)
Objectives: This study aimed to investigate the postoperative quality-of-life of patients with placental adhesion disorder undergoing a cesarean hysterectomy and partial uterine resection. Methods: This was a prospective study performed on 40 patients aged from 25 to 35 years. The subjects were divided into two groups based on whether the uterus was preserved or not following a cesarean hysterectomy and on partial uterine resection. The Turkish version of SF-36 Quality-of-life Scale consisting of 36 items and 8 subscales was applied to the patients. Results: The participants had a mean age of 31.3  ±  3.2 years. The mean parity, number of cesarean sections and body mass index was 3.45, 3.22 and 29.1  ±  2.9, respectively. The mean physical function score was 83.4  ±  11.61 in the cesarean hysterectomy group and 93.67  ±  8.55 in the partial uterine resection group. A significant difference was found between the cesarean hysterectomy and partial uterine resection groups in terms of their health-related quality-of-life (p  =  0.005). Conclusions: Patients who underwent partial uterine resection had improved health-related quality-of-life compared to patients who had a cesarean hysterectomy. Choosing uterus-preserving surgery in suitable patients by evaluating the degree of placental adhesion and adhesion size may have a positive effect on the quality-of-life after surgery.